Ecuador Macroeconomic Stability and Competitiveness Challenges - World Bank (World Bank, Washington, DC, 2019)
Ecuador faces the challenge of consolidating the social gains achieved during the last decade while addressing the excesses committed the commodity boom period, when the state was the main drive of economic growth and the private sector remained subdue. This policy note diagnoses the nature of the imbalances faced by Ecuador’s economy and identifies key areas for reform that will contribute to reestablishing macroeconomic stability and increase the competitiveness, while safeguarding recent social gains. Increasing competitiveness and productivity will require complementing fiscal efforts with core supply side reforms to create a flexible and conducive regulatory environment for the private sector. Pursuing the integration and internationalization of the Ecuadorian economy is a key to foster a private sector-led and productivity-driven economic model going forward. This note identifies key areas that can be considered as part of a medium-term reform agenda to reestablish macroeconomic stability and increase the competitiveness of the Ecuadorian economy, while safeguarding recent social gains. It systematically presents a brief diagnostic together with policy options to be consider within each policy area.